Implementation of green roof technology in residential buildings and neighborhoods of Cyprus. (July 2018) - Ziogou, Isidoros; Michopoulos, Apostolos; Voulgari, Vasiliki; Zachariadis, Theodoros
Highlights: Green roof technology is examined for two different typical residential buildings. Great energy and environmental benefits are achieved against conventional constructions. Sensitivity analysis shows that green roofs become financially favorable with modest reduction in current installation cost. At the neighborhood scale the calculated decrement in air temperature at the pedestrian level is noticeable. Abstract: Green roofs are considered as an appropriate nature-based measure to increase the environmental resilience of cities. This paper examines this technological solution applied to typical urban residential buildings in the Mediterranean island of Cyprus, with respect to energy, environmental, and economic aspects. The analysis shows a clearly positive energy and environmental contribution of green roofs. Although such an investment does not seem to be cost-effective in residential buildings, sensitivity analysis demonstrates that green roofs become financially favorable compared to flat roof constructions with only modest reductions in their current installation cost. Moreover, green roofs offer environmental benefits that are currently difficult to monetize, which can clearly improve urban resilience to climate change. In order to quantify the impact of green roof installations on the surrounding environment, the analysis was expanded from the individual building perspective to neighborhood scale implementation, using appropriate simulation software to evaluate the contribution of green roofs to urban heat island mitigation. Focusing on the ambient air temperature at the pedestrian level, a noticeable decrease was estimated.